Distributor pricing approaches enabled in Smart Grid to differentiate delivery service quality - Jake Zhang, Zhongwei; C Nair, Nirmal-Kumar (EAI Endorsed Transactions on Energy Web, 2014)
Industry practitioners who advocate retail competition and Demand-side Participation now look for approaches to link both initiatives through distributor pricing. As distributors incrementally convert more traditional assets into Smart Grid assets, they also need to consider different pricing approaches to recover the investment costs and meet the regulatory business requirements. Small electricity consumers need incentives to take part in these initiatives but their delivery service quality should also be closely guarded. Hence this paper addresses the above needs as a whole and investigates a set of distributor pricing approaches with Smart Grid technologies. Pricing of network and non-network based solutions should follow the incremental basis, such as the long run average incremental cost (LRAIC). The benefit of deferring network investment is calculated and should be passed to consumers as peak pricing rebate. A concept of reliability premium (RP) based on load point reliability index is proposed, through which customers can express their preference of service quality and adjust their network tariff payment accordingly. A service delivery model is also proposed to utilize the savings from wholesale market trading to compensate for the downgraded service when loads are controlled. The IEEE 123-node distribution test feeder and the IEEE distribution system for RBTS Bus No. 2 are simulated, and solved using General Algebraic Modeling System (GAMS) to demonstrate the proposed distributor pricing approaches in Smart Grid.
Keywords: Asset management; load management; power distribution; power system economics; power system reliability